(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Stroke is the third most common cause of death in the developed world as well as is the most common cause of severe physical disability. A good number of studies have shown elevated serum D-Dimer level in acute ischemic stroke. Approximately one quarter of ischemic strokes are caused by lacunar infarct. This study demonstrated serum D-Dimer in Lacunar Stroke. The purpose of the study to find out serum D-Dimer in Lacunar Stroke. Materials and methods: This cross-sectional study was conducted in Medicine Department, Dhaka Medical College, Dhaka on the patients with diagnosis of first ever acute lacunar Ischemic (LACI) stroke presented within 2 days of onset of symptoms. In this study, total 45 acute LACI cases irrespective of their gender were included and examined in presence of consultant physician, who were admitted from March 2014 to September 2014. Results: An overall male predominance with a male to female ratio was 2:1 with the mean (SD) age of the study population of lacunar stroke was 57.60 (12.68) years. At the distribution of common risk factors in this study, there were hypertension (n=26, 57%), smoking (n=18, 40%) Diabetes mellitus (n=14, 31.1%), dyslipidemia (n=12, 26.6%) and ischemic heart disease (n=9, 20. %). Accounting the focus point of our study, the mean (SD) value of serum D-Dimer was 0.37 (0.20) mg/L with gender difference in male and female [0.39 (0.20) mg/L Vs. 0.31 (0.19) mg/L]. A regression analysis was done to find the association of D-Dimer category group (Dependent variable) which were categorized as Normal range [D-Dimer level <0.5 mg/L (n=29)] and Increased level [D-Dimer level ³0.5 mg/L (n=16)] according to normal cutoff point of D-Dimer (<0.5 mg/L). It shows there was no statistically significant difference among normal and raised D-Dimer with gender, age, smoking, Tobacco, family history of CVD, hypertension, Diabetes mellitus, and dyslipidemia (p value > 0.05). But here, male and dyslipidemia patients were respectively 3.23 and 3.84 times more prone to develop increased level of D-Dimer, but it was statistically nonsignificant. Conclusion: In this study, it was found that serum D-Dimer was not significantly raised with Lacunar stoke patients. Though lacunar stroke is diagnosed specially by imaging methods, serum D-Dimer may play a role in diagnosis process to exclude from non-lacunar stoke. Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 30-34